Essays on economics of airline alliances - Xie, Xin (Kansas State University, 2014)
This dissertation constitutes two essays in the field of industrial organization. Specifically, the research focuses on empirically assessing the market effects of airline alliances. The first essay examines how codesharing, a form of strategic alliances, by airlines affects market entry decisions of potential competitors. Researchers have written extensively on the impact that strategic alliances between airlines have on airfare, but little is known of the market entry deterrent impact of strategic alliances. Using a structural econometric model, this essay examines the market entry deterrent impact of codesharing between incumbent carriers in U.S. domestic air travel markets. We find that a specific type of codesharing between market incumbents has a market entry deterrent effect to Southwest Airlines, but not other potential entrants. Furthermore, we quantify the extent to which market incumbents’ codesharing influences market entry cost of potential entrants. The second essay examines the effects of granting Antitrust Immunity (ATI) to a group of airlines. Airline alliance partners often want to extend cooperation to revenue sharing, which effectively implies joint pricing of their products (explicit price collusion). To explicitly collude on price, airlines must apply to the relevant government authorities for ATI (U.S. Department of Justice and Department of Transportation in the case of air travel markets that have a U.S. airport as an endpoint), which effectively means an exemption from prosecution under the relevant antitrust laws. Whether consumers, on net, benefit from a grant of ATI to partner airlines has caused much public debate. This essay specifically investigates the impact of granting ATI to oneworld alliance members on their price, markup, and various measures of cost. The evidence suggests that the grant of ATI facilitated a decrease in partner carriers’ marginal cost, and increased (decreased) their markup in markets where their service do (do not) overlap. Furthermore, member carriers’ price did not change (decreased) in markets where their services do (do not) overlap, implying that consumers, on net, benefit in terms of price changes.
Keywords: Entry deterrence; Strategic alliances; Dynamic entry/exit model; Airline competition; Antitrust immunity; Economics (0501)